The development of a factor based instrument to measure corporate entrepreneurship: A South African perspective - C. J. Goosen; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 2002)
This article outlines a conceptual model of corporate entrepreneurship in which management's influence on an organisation is highlighted. The model is intended to depict the organisational elements that relate to South African industrial organisations. Corporate entrepreneurship or intrapreneurship is represented by a set of three `key factors'. Two key factors were taken from the well researched ENTRESCALE (Knight, 1997) and focus externally. The other key factor focuses internally and represents management's influence on structures and processes, and relations.The model encompasses product lines and changes, research and development leadership, new techniques employed in the organisation, the organisation's competitive posture and its risk-taking propensity, its environmental boldness and the decision-making style of management in terms of external opportunities. The model also addresses internal structures and processes, as well as relations. It emphasises intrapreneurial goal setting, and promotes the use of a system that facilitates and manages creativity and innovation. It addresses an intracapital system to supply resources and it facilitates communication. The model allows for staff input to management, a degree of intrapreneurial freedom, a problem-solving culture and empowered staff. Finally, it provides for the championing of intrapreneurship by management.The model is tested in context. There is significant negative correlation between intrapreneurship and organisational age, but not between the intrapreneurship and organisation size. The intrapreneurship factors furthermore correlate significantly with the measure of share price volatility, β (Beta).
Keywords: 650